2009
DOI: 10.1080/00016480802412813
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography findings in large vestibular aqueduct syndrome

Abstract: Of the 23 patients (bilateral in 22 and unilateral in 1), additional inner ear malformations were identified in 21 cases presenting either singly or in combination. A small LSCC bony island (<3 mm in diameter) appeared highly typical; vestibule and LSCC anomalies were identified in 13 cases (26 ears) based on visual inspection combined with abnormal measurements. Dehiscence of the superior and/or posterior semicircular canal was identified in 19 ears, and Mondini deformity was identified in 6 ears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…reported a case of SSCD in a young child at the age of 12 years and suggested that SSCD is a developmental defect. The co-existence of SSCD and EVA further supported this developmental hypothesis ( Ma et al., 2009 , Zhou et al., 2007 ). The present study revealed that the average width of vestibular aqueduct is 0.4 at midpoint and 0.5 at opercular site, which is far below the value for EVA ( Boston et al., 2007 ).…”
Section: Discussionsupporting
confidence: 63%
“…reported a case of SSCD in a young child at the age of 12 years and suggested that SSCD is a developmental defect. The co-existence of SSCD and EVA further supported this developmental hypothesis ( Ma et al., 2009 , Zhou et al., 2007 ). The present study revealed that the average width of vestibular aqueduct is 0.4 at midpoint and 0.5 at opercular site, which is far below the value for EVA ( Boston et al., 2007 ).…”
Section: Discussionsupporting
confidence: 63%
“…A few case reports and series have documented SCDs in children [9, 1316, 18, 20]. In children with enlarged vestibular aqueduct syndrome, SCDs have been documented as early as 3 months of age by HRCT [19]. Chen et al [18] in (1993) found a 13.7% rate of superior SCD in children ages 3–17 years.…”
Section: Discussionmentioning
confidence: 99%
“…The only report in the English Literature of one case of EVA and contralateral SSCD included standard axial and coronal CT images [17]; the absence of reformatted reconstruction along the plane of SSC could leave some doubts about the real presence of dehiscence of SSC in this case. On the contrary, the axial plane is able to detect EVA, but some Authors [18] proposed that 458 oblique plane could give a more reliable depiction of the vestibular aqueduct than the axial plane, especially in cases of borderline enlargement of the vestibular aqueduct.…”
Section: Discussionmentioning
confidence: 86%